Preconditioning mesenchymal stromal cells with flagellin enhances the anti‑inflammatory ability of their secretome against lipopolysaccharide‑induced acute lung injury - Li, Rui; Li, Yu; Dong, Xiaoyan (Molecular medicine reports, 2020)
Acute lung injury (ALI) is a complex condition frequently encountered in the clinical setting. The aim of the present study was to investigate the effect of conditioned media (CM) from human adipose‑derived mesenchymal stromal cells (MSCs) activated by flagellin (F‑CM), a Toll‑like receptor 5 ligand, on inflammation‑induced lung injury. In the in vitro study, RAW264.7 macrophages treated with F‑CM had a higher proportion of cells with the M2 phenotype, lower expression of pro‑inflammatory factors and stronger expression of anti‑inflammatory genes compared with the CM from normal adipose‑derived MSCs. Furthermore, in vivo experiments were performed in mice with ALI induced by intraperitoneal injection of lipopolysaccharide. F‑CM significantly alleviated the lung exudation, inhibited inflammatory cell recruitment in lung tissues and decreased the concentration of inflammatory factors in the bronchoalveolar lavage fluid. These findings indicated that F‑CM has superior anti‑inflammation ability compared with CM, and that it may represent a promising therapeutic approach to the treatment of inflammation‑induced ALI.
Gesehen am 05.08.2025